First Successful In Vitro Fertilization At The National Maternal Perinatal Institute. May 2015 - Garnique-Moncada, Marco (2015)
In Vitro Fertilization (IVF) is an assisted reproduction procedure of high complexity that we use in the management of the infertile couple. The aim of this article is the dissemination of the first IVF in a public institution such as the National Maternal and Perinatal Institute, resulting in the birth of two normal newborns.